VISUAL BASIC AS SUPPORTING THE PRESENTATION OF INFORMATION SYSTEM APPLICATIONS ON THE CONSOLIDATED LOAN PORTFOLIO IN THE BANK PT INDONESIAN EXPORTS - Widodo Widodo; Fitri Sjafrina, SKom, MM (Jurnal Sistem Informasi, 2004)
In managing the information of credit data today is still done manually by using microsoft excel, later writers trying to create an application system that replaces the manual system on credit data management at PT Bank Indonesia (Persero), which the authors are currently employed.The system generated a report expected to produce fast, precise and accurate, so it can be used by the leaders in the context of decision making.